INTEGRATING EMOTIONAL INTELLIGENCE AND JOB SATISFACTION TO IMPROVE HEALTHCARE SERVICE DELIVERY: A COMPREHENSIVE STUDY IN TRADITIONAL HEALTHCARE SETTINGS - Phalguni; Malik, Ajmer Singh; Chand, Gian (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Job satisfaction is widely acknowledged as a crucial component that affects the delivery of healthcare services. However, the impact of emotional intelligence (EI) on job satisfaction in traditional healthcare settings has not been thoroughly investigated. This study aims to examine the relationship between healthcare professionals’ emotional intelligence, and job satisfaction, and their impact on the quality of healthcare services, patient outcomes, and workplace harmony.